Implications of a renewable fuels standard - Monoson, Ted (Kansas State University, 2011)
During the past 10 years, ethanol production in the United States has grown exponentially. From 2000 to 2009 U.S. ethanol production increased from 1.6 billion gallons annually to 10.8 billion gallons annually. In 2010, U.S ethanol production increased by 23 percent from 2009 to 13.23 billion gallons. The increase in ethanol production was due to lawmakers reacting to skyrocketing oil prices by implementing a Renewable Fuels Standard (RFS) in 2005 and expanding the RFS in 2007. The RFS requires the use of specified amounts of biofuels, such as ethanol, through the year 2022. The creation of the RFS represented a step beyond lawmakers’ usual policy of using the tax code to promote ethanol production. There is a long history of encouraging ethanol production by using the tax code, but the implementation of a biofuels mandate is new and therefore there is not a great deal of research on the effects of such a policy. This study analyzes U.S. oil, unleaded gasoline, corn and ethanol prices dating back to 1985 to determine the impact that the RFS has had on corn prices. The key question answered is whether the creation and expansion of the RFS has brought the instability of the oil market into the corn market. The prices that an ethanol plant in western Kansas paid for the grain it used to produce ethanol and the price that the plant received for the ethanol that it produced are also analyzed. The plant began operation in January 2004, so it is possible to analyze the grain and ethanol prices both before and after the implementation and expansion of the RFS. To study the impact of the RFS creation and expansion, the prices were analyzed to see if there was an increase in the correlation after the creation and expansion of the RFS. Regression analysis of the national corn prices and the prices that Western Plains Energy paid for the grain that it used to produce ethanol; and regression analysis of the national price of ethanol and the price that Western Plains Energy sold its ethanol for were also used to study the impact of the RFS. Finally, the vector autoregression (VAR) model is used to analyze the dynamic relationships between the variables in the system: corn price, oil price, ethanol price and unleaded gasoline price. The analysis of the correlation reveals that both at the national and plant level grain and oil prices track much more closely together after the creation and then expansion of the RFS. The VAR reveals that there is some relationship between corn and oil prices contemporaneously. The correlation matrix of residuals reveals that there is not a strong correlation between national corn and oil prices. The results suggest the need for greater research in this area. The creation and expansion of the RFS represented a step into uncharted territory and the consequences are still not known.
Keywords: Oil; Ethanol; Renewable Fuels Standard; Vector Autoregression; Corn; Agriculture, General (0473); Economics, Agricultural (0503); Energy (0791)